Kardiochirurgia dorosłychThe results of surgical left ventricular restoration - Deja, Marek; Janusiewicz, Piotr; Biernat, Jolanta; Malinowski, Marcin; Gołba, Krzysztof S.; Domaradzki, Wojciech; Bachowski, Ryszard; Jasiński, Marek; Ceglarek, Wojciech; Woś, Stanisław (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2008)
Aim: To assess early and late results of surgical ventricular reconstruction (SVR). Material and Methods: Over 8 years we operated on 102 patients (75 males) of mean age 63±7. Initial LVEDV was 219±65 ml, ESV 150±55 ml, and EF 32±8%. In 53 patients (52%) we used patches to perform SVR. On average 2.9±1.1 coronary artery bypass grafts were implanted per patient (min. 0 – max. 5). In 43 (42%) patients we performed MV repair, in 1 MVR, in 4 TV repair, in 1 post-infarction VSD repair, in 1 ASD repair, in 1 AVR and in 1 ascending aorta replacement. Results: There were 8 perioperative deaths (7.8%). One-, 2-, 3-, and 5-year survival was: 83±5%, 76±5%, 72±6% and 62±7% respectively. As a result of SVR EDV dropped to 172±52 ml (p<0.001), ESV to 112±50 ml (p<0.001) and EF increased to 37±11% (p=0.053) in the last echocardiographic follow-up. On the last visit NYHA class was 1.6±0.7 – significantly less than preop 2.1±0.9 (p=0.009), and CCS class 0.6±0.6, less than preoperative 1.6±1.2 (p<0.001). Mitral valve repair increased perioperative mortality, 13.9% vs. 3.4% (p=0.1), and late mortality: 3-year survival 63±8 vs. 80±8% (p=0.04). The influence of higher preoperative LV volume was not significant on survival. In multivariate analysis LV EF <30% increased late mortality – OR 3.0 (95% CI 1.1-7.7) p=0.02. Conclusions: SVR may be added to CABG in ischaemic cardiomyopathy with reasonable operative risk. Long-term survival of our patients appears less than in the RESTORE group. The influence of SVR on long-term survival requires assessment in randomized trials.